When steroids are not enough in immune-related hepatitis: current clinical challenges discussed on the basis of a case report - Paolo Antonio Ascierto; Amalia Anastasopoulou; Helen Gogas; Evangelos Cholongitas; Panagiotis Diamantopoulos; Aikaterini Gkoufa (Journal for ImmunoTherapy of Cancer)
Unleashing adaptive immunity via immune checkpoint inhibitors (ICPIs) in many cancer types led to durable antitumor responses and prolonged survivals and also added some new immune-related adverse events (irAEs) to the ‘old-fashioned’ safety profile of chemotherapy. Among bowel and endocrine irAEs, immune-mediated hepatotoxicity/hepatitis is a less common and far less well-studied toxicity, which, however, could develop into a serious complication, especially when it becomes persistent or refractory to steroids. Its incidence, onset and severity vary widely, depending on the type of underlying treated cancer, the class, the dosage and the duration of immunotherapy as well as the way of its administration (as a single agent or in combination with other ICPI or chemotherapy). In this study, we present a patient with metastatic melanoma who developed severe steroid-resistant ir-hepatitis after treatment with ipilimumab and required triple concurrent immunosuppression with prednisolone, mycofenolate mofetil and tacrolimus in order for his liver toxicity to be resolved. Intrigued by this case, we focused further on melanoma, as the disease-paradigm of immunotherapy in cancer, reviewed the reported incidence of hepatotoxicity among phase III ICPIs-containing trials on melanoma and discussed the main clinical considerations regarding the diagnosis and the management of persistent/steroid-refractory ir-hepatitis. As more clinical experience is gradually gained on this challenging topic, better answers are provided to questions about the appropriate diagnostic workup, the necessity of liver biopsy, the available immunosuppressive options beyond corticosteroids (their combinations and/or their sequence) as well as the correct decision on withdrawing or resuming immunotherapy. Nonetheless, a thorough multidisciplinary discussion is still required to individualize the overall approach in each case after failure of steroids.